Warping constant of steel section - Yong, Jitt Ching (2003)
This project report is aimed to study the warping behaviour of steel section. The main objective of this study is to obtain relationship of warping displacement and warping constant. In BS5950, there is already a basic derivation of warping constant with its relationship with the geometry of cross section. Somehow, this formula is unsuitable to be applied for some section member such as corrugated I-beam. Modifying the formula needs a lot of study and research; it is not economic both in cost and time. To overcome this, there comes a suggestion. There might be a relationship between warping displacements of member with different cross section as they are using the same material. By developing a relationship between warping constant and warping displacement, it is easy to find the warping constant of abnormal section with condition that we know its warping displacement. But, there is no reference available for the relationship governing the warping constant and warping displacement. In order to achieve the objectives, finite element analysis is camed out. Each parameter that affects the warping displacement and warping constant is under the consideration and been studied.